2007
DOI: 10.1097/01.qai.0000243113.29412.dd
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Antiretroviral Care Is Associated With Positive Social Outcomes in a Prospective Cohort in Uganda

Abstract: Participation in a home-based antiretroviral therapy program was associated with multiple positive social outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…In contrast, a woman in Uganda reported a decrease in her husband’s IPV perpetration as his illness progressed, though not when they both tested positive for HIV [96]: “She thought their illness would improve the relationship, but it did not. The main change came after the man began falling sick and lost energy, “after a while he was weak and did not have the energy to beat me.”” IPV did not significantly increase with initiation of home-based ART in a study of women with HIV in Uganda [13]; rates of physical IPV were 1% (3/459) in the three months before ART initiation and 2% (9/436) in the three months after program initiation, with an unadjusted OR of 3.20 (95% CI 0.94-10.9, p=0.063), though notably, 5 (1%) of the 436 women reported physical violence associated with program participation.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, a woman in Uganda reported a decrease in her husband’s IPV perpetration as his illness progressed, though not when they both tested positive for HIV [96]: “She thought their illness would improve the relationship, but it did not. The main change came after the man began falling sick and lost energy, “after a while he was weak and did not have the energy to beat me.”” IPV did not significantly increase with initiation of home-based ART in a study of women with HIV in Uganda [13]; rates of physical IPV were 1% (3/459) in the three months before ART initiation and 2% (9/436) in the three months after program initiation, with an unadjusted OR of 3.20 (95% CI 0.94-10.9, p=0.063), though notably, 5 (1%) of the 436 women reported physical violence associated with program participation.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of stigma, an RCT reported that only 3 % of patients refused to participate in the home-based ART program due to stigma [25]. Furthermore, it has even been suggested that involvement of community-health care workers in HIV care reduced stigma [72] and being part of peer groups has been found to decrease the perception of social stigma [73]. …”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that novel strategies to bring HIV services to the community level through task shifting, such as home-based HIV testing [52][55] and home-based ART initiation [56] and delivery [57][61] are effective, feasible and acceptable [62]. In addition, positive side effects of home-based ART delivery programs include increased community-level social support and decreased discrimination [61], [63], and clients of these services reported saving time and money due to reduced clinic visits [64]. These novel community-based strategies would require significant political commitment and operational research to tailor programs to the local context, but may have the potential to strengthen all stages of the HIV care continuum by improving identification of HIV-infected individuals, simplifying linkages to care, improving retention in ART care programs, and reducing structural-level barriers such as distance, cost and stigma and discrimination.…”
Section: Discussionmentioning
confidence: 99%